Comparison of Disturbance Compensators for a Discrete-Time System with Parameter Uncertainty - Zhongyi Guo; Haifeng Ma; Qinghua Song (Applied Sciences, 2020)
The control design for many industrial applications requires compensation for parameter uncertainty and external disturbance. Reported in many previous works, the parameter uncertainty and external disturbance are combined as a lumped disturbance, which is assumed to be smooth and bounded. However, for a discrete-time sliding mode control (DSMC) system, the above assumption may not hold. Here, the parameter uncertainty, along with its compensation in the DSMC system, are reconsidered and reevaluated. The influence of parameter uncertainty on the closed-loop system stability is first addressed. Then, the comparative investigation of the performance of six state-of-the-art disturbance compensators for parameter uncertainty compensation is conducted. Simulation results show that none of these compensators can effectively observe and compensate for the parameter uncertainty.